Cortical Serotonergic and Catecholaminergic Denervation in MPTP-Treated Parkinsonian Monkeys. (14th September 2021) - Masilamoni, Gunasingh Jeyaraj; Weinkle, Allison; Papa, Stella M; Smith, Yoland
Abstract: Decreased cortical serotonergic and catecholaminergic innervation of the frontal cortex has been reported at early stages of Parkinson's disease (PD). However, the limited availability of animal models that exhibit these pathological features has hampered our understanding of the functional significance of these changes during the course of the disease. In the present study, we assessed longitudinal changes in cortical serotonin and catecholamine innervation in motor-symptomatic and asymptomatic monkeys chronically treated with low doses of 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP). Densitometry and unbiased stereological techniques were used to quantify changes in serotonin and tyrosine hydroxylase (TH) immunoreactivity in frontal cortices of 3 control monkeys and 3 groups of MPTP-treated monkeys (motor-asymptomatic [ N  = 2], mild parkinsonian [ N  = 3], and moderate parkinsonian [ N  = 3]). Our findings revealed a significant decrease ( P  < 0.001) in serotonin innervation of motor (Areas 4 and 6), dorsolateral prefrontal (Areas 9 and 46), and limbic (Areas 24 and 25) cortical areas in motor-asymptomatic MPTP-treated monkeys. Both groups of symptomatic MPTP-treated animals displayed further serotonin denervation in these cortical regions ( P  < 0.0001). A significant loss of serotonin-positive dorsal raphe neurons was found in the moderate parkinsonian group. On the other hand, the intensity of cortical TH immunostaining was not significantly affected in motor asymptomatic MPTP-treated monkeys, but underwent a significant reduction in the moderate symptomatic group ( P  < 0.05). Our results indicate that chronic intoxication with MPTP induces early pathology in the corticopetal serotonergic system, which may contribute to early non-motor symptoms in PD.